Isolation, characterisation and in vitro screening of anticataract potential of Fucoidan from Sargassum wightii Greville - Sathiya Ramu; Shah Akshay Mahendra; Keerthana Kunchakuri; Pooja P. Karadi; Kumari Swetha; Gowri Radhakrishnan (Shahrekord University of Medical Sciences, 2018)
Introduction: The present study was designed to isolate Fucoidan from Sargassum wightii Greville and to evaluate its in-vitro anti cataract potential against galactose induced cataract in isolated goat lenses. Methods: Fucoidan was isolated from S. wightii Greville and its sulfate content was estimated through barium chloride method. Isolated goat lenses were divided into 5 groups as group-I (normal control- vehicle treated), group-II (disease control- galactose treated 55 mM), group-III (galactose 55 mM + standard-ascorbic acid 20 μg/mL), group-IV (galactose 55 mM + Fucoidan-20 μg/mL) and group-V (galactose 55 mM + Fucoidan 40 μg/mL) and incubated for 72 hours, respectively, and subjected to biochemical estimations. The opacity of lenses was also noted prior to biochemical estimation. Results: The percentage yield of isolated Fucoidan was found to be 0.65%. The extent of sulfation in the isolated Fucoidan was found to be as high as 33%. In high-performance thin-layer chromatography (HPTLC) studies, Peak 3 with Rf value of 0.18 matched with the standard D-glucose Rf value. Galactose induced cataractous lenses showed significant oxidative stress when compared to normal lenses whereas treatment with Fucoidan 20 and 40 μg/mL significantly combated oxidative stress and prevented the development of cataract when compared to cataractous lenses. The results obtained with the treatment of Fucoidan were dose dependant and comparable to standard. Conclusion: The present study substantiates the claim of anti-cataract potential of Fucoidan, which may be correlated to its anti-oxidant property.